Pengaruh Bahan Ajar Audio-Visual Aids (AVA) Dalam Mata Pelajaran Sejarah Kebudayaan Islam Terhadap Peningkatan Prestasi Belajar Siswa - Raito, Raito; Hayah, Ismi Ismatul; Abdullah, Deba Muslim (MASAGI : Jurnal Pendidikan Agama Islam, 2024)
Academic achievement is the assessment of learning outcomes expressed in the form of symbols, numbers, letters, or sentences that reflect the results achieved by students. Currently, student performance in the subject of Islamic Cultural History remains low, with some students scoring below the Minimum Completeness Criteria (KKM). Audio-visual aids are teaching materials used in the learning process to convey information or concepts through the use of sound, images, and motion. These aids are designed to provide a more interactive and engaging learning experience, facilitating students' understanding of the material being taught. This study aims to describe the impact of using audio-visual aids in Islamic Cultural History lessons on improving students' academic achievement. The research method employed is experimental, specifically a quasi-experimental design with a pre-test post-test control group setup. Data collection techniques included observation, questionnaires distributed to 68 students, and document study. Data processing was conducted using statistical analysis. The results of the study indicate that the average pre-test score for the experimental group was 58.794, while the control group scored 58.205. After the intervention using problem-based learning with audio-visual aids, the post-test average in the experimental group increased to 69.529, whereas the control group's average, which did not use audio-visual aids, was 61.235. Based on the t-test results, the value of t_calculated > t_table (t_calculated = 4.489 > t_table = 1.996). Therefore, it can be concluded that there is a significant effect of audio-visual aids on the academic achievement of students in the Islamic Cultural History subject in the Xth grade at MA Fauzaniyyah Sukaresmi Garut. Keywords : Audio-Visual Aids, Islamic Cultural History, Student Academic Achievement